THE CELLULAR AND HUMORAL IMMUNITY STATE DEPENDING ON THE OUTCOME OF A WIDESPREAD PURULENT PERITONITIS - A. A. Savchenko (Sankt-Peterburg : NIIÈM imeni Pastera, 2015)
The aim of the study was to examine the state of cellular and humoral immunity in patients with widespread purulent peritonitis (WPP) in depending on the disease outcome. The study involved 50 patients with community-acquired and hospital origin WPP. The testing of blood lymphocyte phenotype was performed by flow cytometry. The concentration of immunoglobulins and cytokines were measured by ELISA. It was established that the immune system state by WPP is characterized by leukocytosis, relative lymphopenia, increasing concentrations of pro-inflammatory cytokines, as well as decrease of the cytotoxic and activated T-lymphocytes content. The state of the cellular immunity in case of unfavorable outcome of the WPP is characterized by decreased of the γδT-lymphocytes and NKT-cells levels with increasing amounts of the B1-cells. The immune system state in case of a favorable outcome of the WPP is characterized by a decrease in the number of NK-cells in peripheral blood and increased levels of Th2-lymphocytes. Increasing of the Th2-cells number determines the increase in stimulating effects of T-cell on the humoral immunity, that is manifested in increasing concentrations of IL-4 and IgA, which is an important factor in the immunopathogenesis of the WPP determining its favorable outcome.